Aspek Hukum dan Fiqih Tentang Transaksi Organ Tubuh Untuk Transplantasi Organ Tubuh Manusia - Sri Ratna Suminar (Fakultas Hukum, Universitas Islam Bandung, 2010)
Now days, the need of human organs for transplantation is decreasing, meanwhile the availability of human organs is very limited, therefore such situation may cause the business transaction between donor and recipient. However there is no clear distinction whether human organ is a goods or things, meanwhile civil code use term of goods inconsequently. The civil code does not classify human organ as business transaction object. Therefore, every transaction on this object is illegal. It breaks the Law number 36 Year 2009 regarding health and the government regulation number 18 Year 1981. Furthermore, accordance to Islamic law, position of human organ is clear that it is not a property (‘ain ghairu qimatin). Then, according to syar’I, it cannot be as an object in any business transaction.